The training characteristics of world-class male long-distance cross-country skiers - Torvik, P.-Ø.; Solli, G. S.; Sandbakk, O. (Frontiers in Sports and Active Living, 2021)
Purpose: To investigate the training characteristics of world-class long-distance cross-country skiers.